Hydrolysis of glucose in Kenaf biomass - Anuar, Hazleen; Mel, Maizirwan (s.n, 2012)
Kenaf (Hibiscuss cannabinus.L) is one of lignocellulosic materials in which are classified into biomass since it contains cellulose, lignin and hemicelluloses. Due to its complex structure,it cannot be directly converted into end products such as ethanol and lactic acid. It has to undergo pre-treatment process. Basically, the pre treatment process is on kenaf fibre with different concentration of Sodium Hydroxide (NaOH), Sulfuric Acid (H2SO4) and Ammonia (NH3) to hydrolyze the cellulose content in fibres. The pre-treatment results show that mild H2SO4 hydrolysis is found to be the best pre-treatment method since it liberates the maximum glucose content compared to others. In this study, the optimization of the glucose content from this pre-treatment process occurs when the mass of raw material is 3g, its temperature is 160oC and the time taken to hydrolyse is 35 minutes.